2014
DOI: 10.1080/02705060.2013.873882
|View full text |Cite
|
Sign up to set email alerts
|

Effects of colonialMicrocystis aeruginosaand interspecific competition on the population dynamics and resting egg formation of two cladocerans

Abstract: We investigated the effects of colonial Microcystis aeruginosa and interspecific competition on the population dynamics and resting egg formation of two cladocerans. In the single-species culture experiments, high M. aeruginosa concentrations favored the population growth of Moina irrasa but strongly inhibited that of Daphnia carinata. Small-bodied M. irrasa was predominant over large-bodied D. carinata regardless of the presence of the colonial M. aeruginosa in the mixed cultures. The per capita cumulative nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Although many toxicity tests with cyanobacteria and zooplankton have already been carried out (Hanazato and Yasuno, 1987;Fulton and Paerl, 1988;Billoir et al, 2009;Cerbin et al, 2010;Shao et al, 2014), but the mechanism action of these substances on the zooplankton remains little known. In addition to the nutrient enrichment originated from the above causes, the continuous supply of pollutants such as hormones (Hense et al, 2004), drugs (Flaherty and Dodson, 2005) and pesticides (Hanazato, 2001) may decrease the organism reproduction rate, causing the removal of larger species, interfering in the energy transference of food chain (Sibley and Hanson, 2011) and in the biogeochemical cycles (Henry et al, 2004;Romo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Although many toxicity tests with cyanobacteria and zooplankton have already been carried out (Hanazato and Yasuno, 1987;Fulton and Paerl, 1988;Billoir et al, 2009;Cerbin et al, 2010;Shao et al, 2014), but the mechanism action of these substances on the zooplankton remains little known. In addition to the nutrient enrichment originated from the above causes, the continuous supply of pollutants such as hormones (Hense et al, 2004), drugs (Flaherty and Dodson, 2005) and pesticides (Hanazato, 2001) may decrease the organism reproduction rate, causing the removal of larger species, interfering in the energy transference of food chain (Sibley and Hanson, 2011) and in the biogeochemical cycles (Henry et al, 2004;Romo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Many previous investigations had indicated that the body length of Daphnia declined with increased M. aeruginosa concentrations [7,9,18], including the body length at maturity [13,21,25]. Cerbin et al [4] found also that increasing microcystin concentrations significantly reduced the body length at first reproduction of D. pulicaria.…”
Section: Discussionmentioning
confidence: 95%
“…In subtropical reservoirs, the toxin and colonial morphology of Microcystis reduced net reproductive rate and intrinsic rate of population increase in Daphnia geleata [13]. The number of offsprings at first reproduction of D. carinata decreased with increasing M. aeruginosa biomass [25]. Some previous investigations had found that M. aeruginosa from Lake Chaohu contained microcystins, which it was toxic to Daphnia [3,16,27].…”
Section: Discussionmentioning
confidence: 95%
“…6A), suggesting that M. aeruginosa may impair the ability of D. magna to produce sufficient energy through hampered AK expression. Cyanobacteria, including Microcystis, are well-known to be of low food quality for zooplankton due to its toxicity (Lampert, 1981), mechanical interference (Shao et al, 2014), or nutritional deficiencies (Müller-Navarra, 1995. The inhibited AK expression could not be due to mechanical interference given that the M. aeruginosa strain used in this study grew as single cells.…”
Section: Discussionmentioning
confidence: 99%